PENINGKATAN LITERASI MEMBACA SISWA SEKOLAH DASAR MELALUI KEGIATAN LOMBA “GEMBIRA” - Fanida Zahrotul Muhfidah; Dewi Tryanasari; Agista Faraditya Megananda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This community service activity aims to improve the reading literacy and storytelling skills of elementary school students through the GEMBIRA Program (Story Reading Movement). The low ability of students to understand reading and retell the storyorally is the background for the implementation of the GEMBIRA Program. The method used is literacy socialization and storytelling competitions held for students in grades 1–6 of Kendung Elementary School, Ngawi Regency. The activity beganwith observing students' literacy skills, preparing materials and assessment rubrics, conducting storytelling competitions, and evaluating them through pretests and posttests. The results of the activity showed an increase in students' self-confidenceand ability to understand reading as well as skills in telling stories coherently and expressively. This community service activity also produced outputs in the form of documentation and literacy learning materials that can be used sustainably by theschool. Thus, the GEMBIRA Program is considered effective as a strategy for strengthening basic literacy and developing elementary school students' communication skills.